Habits in Consumption, Transactions Learning and Economic Growth - GURDGIEV, CONSTANTIN (My University, 2005)
This paper presents a model of endogenous growth in the presence of habit formation in consumption. We argue that in addition to the traditional disutility effects of habitual consumption, the past history of consumption represents a past record of transactions as well. As a result, the knowledge acquired in the process of past consumption leads to efficiency gains in allocating time to other activities. In particular, the investment technology in broad household capital can be seen as benefiting from the habitual consumption knowledge, while being subject to the costly new consumption pathways learning. These learning-by-consuming effects imply a faster speed of convergence to the steady state growth rate in consumption and a higher steady state ratio of capital to habits. Alternatively our model allows for the case where new consumption is associated with the accumulation of broad capital, as is consistent with the case where consumption goods can also be used in production. In this case convergence to steady state growth rate is slower.
PUBLISHED
Keywords: Economics; endogenous growth; transactions cost; capital